Persistent Polarizing Effects of Persuasion: Experimental Evidence from Turkey - Baysan, Ceren (American Economic Review, 2022)
I evaluate randomly varied neighborhood exposure to information campaigns regarding either executive performance, or increases in executive power, prior to a Turkish referendum on weakening checks and balances on the executive. The campaigns increased voter polarization over the referendum, and subsequently changed party affiliation in national and local elections over the next two years, leading to partisan polarization. My results suggest that, when voters disagree on whether increasing executive power is a good policy, more information can increase voter polarization. Finally, I conclude that because potential polarization is often ignored, the impact of information campaigns on civil society is underestimated. (JEL D72, D83, O17)